2019
DOI: 10.1507/endocrj.ej18-0291
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile of circular RNAs in placentas of women with gestational diabetes mellitus

Abstract: Forty-five pregnant women who underwent cesarean section, including 30 cases of gestational diabetes mellitus (GDM) and 15 normal pregnant women, were enrolled in this study to examine the differential expression of circular RNAs (circRNAs) in the placentas of women with GDM by RNA sequencing (RNA-seq) analysis. The differentially expressed circRNAs were analyzed bioinformatically using Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment and circRNA-microRNA (miRNA) interaction pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 36 publications
2
59
0
Order By: Relevance
“…Previously, we found that the expression of hsa_circ_0005243 was significantly lower in GDM placenta relative to the control group by high-throughput RNA sequencing (13). qRT-PCR analyses verified these results, showing that the expression of hsa_circ_0005243 was significantly lower in both the placenta (Fig.…”
Section: Characterization Of Hsa_circ_0005243 In Gdmsupporting
confidence: 69%
See 1 more Smart Citation
“…Previously, we found that the expression of hsa_circ_0005243 was significantly lower in GDM placenta relative to the control group by high-throughput RNA sequencing (13). qRT-PCR analyses verified these results, showing that the expression of hsa_circ_0005243 was significantly lower in both the placenta (Fig.…”
Section: Characterization Of Hsa_circ_0005243 In Gdmsupporting
confidence: 69%
“…Emerging evidence has shown that circRNAs are strongly associated with the occurrence and development of preeclampsia, GDM, and other pregnancy-related diseases (11,12). Previously, we reported a significant decrease of hsa_circ_0005243 in the placenta of GDM pregnant women by high-throughput RNA sequencing (13). Here, we investigated the possible regulatory function of this circRNA in the trophoblast cell line HTR-8/SVneo and explored its potential mechanisms of action.…”
Section: Introductionmentioning
confidence: 94%
“…More recently, hsa_circRNA_0054633 was shown to have a closely associated with GDM and a highly diagnostic value for this disorder [78]. Assessment of the expression profile of circRNAs in the placentas of women with GDM revealed that circ_5824, circ_3636 and circ_0395 levels were significantly lower in the GDM group compared to the control group [79]. Taken together, these findings suggest that circRNAs may be associated with the development of GDM and offer a potential for risk prediction and intervention strategies of this disorder, but the underlying mechanisms need further study.…”
Section: Gestational Diabetesmentioning
confidence: 99%
“…Research that focuses on these issues along with the development of a multi-markers approach that combines circRNAs and clinical, genetic, epigenetic, and classical markers may help guide medical decision-making in diabetes state and hold great promise especially in terms of precision medicine. ↑ circRNA_15698/miR-185/TGF-β1 axis promoted extracellular matrix (ECM)-related protein synthesis in diabetic nephropathy progression [71] Gestational Diabetes circ_5824, circ_3636, circ_0395 ↓ Suspected to be involved in the occurrence and pathogenesis of GDM [79] hsa-circRNA_0054633 ↑ Change in its expression in the placental villi of GDM patients may reflect its potential role in the development of GDM [78] Diabetic Retinopathy circRNA-0005015 ↑ Involved in diabetes retinopathy by acting as miR-519d-3p sponge to increase the expression of its target genes, MMP-2, XIAP, and STAT3 [64] circRNA-HIPK3 ↑ Promotes retinal vascular disorders by blocking miR-30a-3p members function to reverse the expression of their target genes VEGF, FZD4, and WNT2 [65] cZNF609 ↑ Role in mediating vascular dysfunction by acting as miR-615-5p sponge [66] circRNA-cPWWP2A ↑ Alleviates diabetes mellitus-induced retinal vascular dysfunction by sponging miR-579 [67] Abbreviations: CVD, cardiovascular disease; FZD4, frizzled class receptor 4; GDM, gestational diabetes mellitus; MYRIP, myosin VIIA and Rab interacting protein; MMP-2, matrix metalloproteinase-2; PAX6, the paired box gene 6; SLC2A2, solute carrier family 2 member 2; STAT3, signal transducer and activator of transcription 3; TGF-β, transforming growth factor-beta; VEGF, vascular endothelial growth factor; T2DM, type 2 diabetes mellitus; VSMCs, vascular smooth muscle cells; WNT2, Wingless-type MMTV integration site family, member 2; XIAP, X-linked inhibitor of apoptosis protein; ↑, up-regulated; ↓, down-regulated.…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%
“…long non-coding RNA, miRNA, circular RNA) in the placenta ( Cox et al , 2015 ). Differential placental expression of non-coding RNAs has been investigated in pre-eclampsia ( Gunel et al , 2017 ; Hu et al , 2018a ; Lykoudi et al , 2018 ; Zhou et al , 2018 ), GDM ( Li et al , 2015 ; Wang et al , 2019b ), IUGR or SGA pregnancies ( Wen et al , 2017 ; Ostling et al , 2019 ) and early pregnancy loss ( Hosseini et al , 2018 ). The use of RNA sequencing technologies to further characterize these non-coding RNAs provides a tantalizing approach to identify and develop new biomarkers and therapeutic targets for pregnancy complications.…”
Section: Knowledge Gaps and Future Directionsmentioning
confidence: 99%